THE IMPORTANCE OF PLAY ACTIVITY IN CHILDREN'S DEVELOPMENT - Nuranova , Gumisay (WORLD INTERNATIONAL CONFERENCE ON SCIENCE, TECHNOLOGY AND EDUCATION, 2026)
This article provides a scientific and pedagogical analysis of the role and importance of play in the development of preschool-aged children. It explores how the process of play influences children's cognitive, social, emotional, and speech development, as well as their formation as individuals.